Implementation of Value Added Tax Policy for Micro, Small, and Medium Enterprises in Indonesia - Noviyanto, Aldy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the implementation of Value Added Tax (VAT) policy on Micro, Small and Medium Enterprises (MSMEs) actors in Indonesia and its impact on tax compliance and business sustainability. The VAT policy implemented by the government has significant implications for the MSME sector which is the backbone of the national economy. The research method used is a qualitative method with a normative juridical approach supported by empirical data from various sources. The results showed that the implementation of VAT policy on MSMEs still faces various obstacles, both in terms of taxpayer understanding, tax administration systems, and supervision from tax authorities. The level of MSME tax compliance is still relatively low due to the complexity of regulations, high administrative burden, and lack of effective socialization. This study also found that VAT policy impacts the cost structure of MSMEs which can affect their competitiveness in the market. The conclusion of this study is the need for MSME-friendly VAT policy reforms with simplified procedures, increased socialization, and strengthening information technology-based supervision systems to improve tax compliance without hindering the growth of the MSME sector.